Public sector reforms and their impact on the level of corruption: a systematic review - Mugellini, Giulia (Campbell Systematic Reviews, 2021)
The main objective of this review is to identify what works in curbing corruption in the public sector, by meta-analyzing the findings of published and unpublished evaluations of different types of anti-corruption interventions in different countries. The focus of this review is administrative corruption, namely corrupt acts involving civil servants in their dealings with their superiors, during the implementation of public policies, or while interacting with the public for service delivery. Political corruption (in the adoption of laws, regulations, and policies), and private-to-private corruption (involving only private actors) are excluded from this review.